(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Sikkim is naturally endowed with rich Hydro Power potential. The State’s generation capacity is contributed solely by the hydro stations. But recent years these stations are encountering increasing number of uncertain weathers, which resulted into shortfall of precipitation during monsoon and higher abnormal rainfall during pre-monsoon times. Though some of the rivers are perennial but these uncertainty are creating challenge for them. More over the state has a large number of Run off river (RoR) hydro systems, which has a limited storage capacity. This is practically impossible to store the amount of water resource required by the hydro power plant through the use of such small pondage system. Neither this practice is permitted. The uncertain whether creates threat to the power supply, in this backdrop the present work aims to integrate the existing RoR hydro power plant with a reasonable amount of solar PV to maintain the supply reliability throughout the year. The present work involves a pre-HOMER analysis of load profile, resources at the site and post-HOMER analysis and discusses issues that are likely to affect/influence the realization of the optimal solution.